Folic acid ameliorates alcohol-induced liver injury via gut–liver axis homeostasis - Zhang, Huaqi; Zuo, Yuwei; Zhao, Huichao; Zhao, Hui; Wang, Yutong; Zhang, Xinyu; Zhang, Jiacheng; Wang, Peng; Sun, Lirui; Zhang, Huizhen; Liang, Hui (Frontiers in Nutrition, 2022)
The gut–liver axis (GLA) plays an important role in the development of alcohol-induced liver injury. Alcohol consumption is typically associated with folic acid deficiency. However, no clear evidence has confirmed the effect of folic acid supplementation on alcohol-induced liver injury via GLA homeostasis. In this study, male C57BL/6J mice were given 56% (v/v) ethanol and 5.0 mg/kg folic acid daily by gavage for 10 weeks to investigate potential protective mechanisms of folic acid in alcohol-induced liver injury via GLA homeostasis. Histopathological and biochemical analyses showed that folic acid improved lipid deposition and inflammation in the liver caused by alcohol consumption and decreased the level of ALT, AST, TG, and LPS in serum. Folic acid inhibited the expression of the TLR4 signaling pathway and its downstream inflammatory mediators in the liver and upregulated the expression of ZO-1, claudin 1, and occludin in the intestine. But compared with the CON group, folic acid did not completely eliminate alcohol-induced intestine and liver injury. Furthermore, folic acid regulated alcohol-induced alterations in gut microbiota. In alcohol-exposed mice, the relative abundance of Bacteroidota was significantly increased, and the relative abundance of unclassified_Lachnospiraceae was significantly decreased. Folic acid supplementation significantly increased the relative abundance of Verrucomicrobia, Lachnospiraceae_NK4A136_group and Akkermansia, and decreased the relative abundance of Proteobacteria. The results of Spearman’s correlation analysis showed that serum parameters and hepatic inflammatory cytokines were significantly correlated with several bacteria, mainly including Bacteroidota, Firmicutes, and unclassified_Lachnospiraceae. In conclusion, folic acid could ameliorate alcohol-induced liver injury in mice via GLA homeostasis to some extent, providing a new idea and method for prevention of alcohol-induced liver injury.